Pharmacognostical Study on Hiptage benghalensis kurz. - Sathis Kumar, D.; Praveen Kumar, T.; Anvesh, J.M.; Kiran Kumar, G.; Banji, David (Asian Journal of Chemistry, 2011)
This paper deals with the pharmacognostical evaluation of the Hiptage benghalensis kurz. Morphology of the entire plant has been studied with the aim to aid pharmacognostic and taxonomic species identification using light and confocal microscopy, WHO recommended physico-chemical, morphological and histological parameters presented in this paper. This study may be proposed as parameters to establish the authenticity of Hiptage benghalensis kurz and can possibly help to differentiate the drug from its other species/varieties.